The factorization method for inverse problems - Kirsch, Andreas, 1953-; Grinberg, Natalia (Oxford : Oxford University Press, 2008)
The 'factorization method', discovered by Professor Kirsch, is a method for solving certain types of inverse scattering problems and problems in tomography. The text introduces the reader to this promising approach and discusses the wide applicability of this method by choosing typical examples.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Inverse problems (Differential equations); Factorization (Mathematics)